28th International Offshore and Polar Engineers Conference (ISOPE 2018) - Michailides, Constantine (My University, 2026)
Secretary of the Scientific Committee "International Offshore Technology Committee (IOTC)" of the annual conference of the organization International Society of Offshore and Polar Engineers (ISOPE).